(untitled) (Research, Society and Development, 2020)
The objective of this work is to analyze the pharmacological activity of the ethanolic extract of the Barbatimão-verdadeiro in the intestinal peristalsis of mice (Mus Musculus). The study is characterized as a quantitative, exploratory and experimental research, in which two pharmacological tests were performed. The animals (n = 35) were treated with a dose of 500mg / kg Stryphnodendron adstringens ethanolic extract and intestinal motility was evaluated following the intestinal transit models (n = 15) and castor oil-induced diarrhea (n = 20). Statistical analysis with one-way ANOVA and Tukey test for significance analysis showed that the group treated with the plant showed significance in relation to the group treated with loperamide (p <0.05). In the induced diarrhea test, the extract showed significance (P = 0.0002) compared with the loperamide treated group and the control group. Therefore, Stryphnodendron adstringens ethanolic extract was effective in reducing intestinal motility.